Nietzsche and Luther: Reading, Counter-Text, Hermeneutics. Issue 1 (April 2021) - Cummings, Brian
Abstract : In what way is Nietzsche's infamous late aphorism, 'God is dead', related to a general attack on theology and its intellectual practices? In Twilight of the Idols, he remarks: 'I'm afraid we're not rid of God because we still believe in grammar.' Reason, he decries, has become mired in linguistic rules long determined by the requirements of scholastic philosophy, whether of medieval theology or of Immanuel Kant. Nietzsche dismisses these as die Sprach-Metaphysik ('metaphysics of language'). In this essay I examine Nietzsche's attack on theology via his long-term struggle with the ideas of Luther, once the idol of Goethe's German enlightenment, and now, Nietzsche insists, its arch-enemy. To do this, I re-examine Luther's theology of language, especially in the early Lectures on Romans (1515–1516). Luther's own attack on scholasticism is founded on a theology of reading which has unexpected affinities with Nietzsche. By placing this in a revised genealogy of hermeneutics from Nietzsche to Heidegger, it is possible to see theology as less deterministic and metaphysical.